Polyamide Nanofibers Coating by Electrospinning Technique for Anti Corrosion Behavior - B.M. Aldabbagh; H.J. Alshimary (Engineering and Technology Journal, 2017)
Poly amide (PA-6) nanofiber coatings on aluminum surface using electrospinning technique under two different voltage (24 kV & 34 Kv) were prepared. The coating morphology , roughness and 3D structural properties tested by using Atomic force microscopes (AFM), surface characterized by (SEM) microscopy, and high resolution optical microscopy (HROM) , Contact angle for hydrophobic behavior was tested by shape drop analyzer , and FTIR analysis for changing in crystalline structure was performed .The AFM images showed that the PA coating on the aluminum surface have a tight and twisted nanofiber structure with some beads through its morphology. SEM images shows the morphology beads of surface nanofibers . The electrochemical corrosion of aluminum without and with PA coating studied by subjected it to aerobic solutions of 3.5 wt.% sodium chloride (NaCl) . It has been found that the PA coatings decrease the corrosion currents and corrosion rate as well as increase the corrosion resistance for aluminum in the NaCl solution .